Character Education: Instilling Positive Values in the Younger GenerationFaizal - Hasbi; Ine Indiyani (Yayasan Baru Haji Samsudin, 2025)
CCharacter education plays a vital role in shaping the younger generation into individuals with integrity, morality, and ethical awareness. Developing positive values such as honesty, responsibility, empathy, and respect is essential not only for personal growth but also for fostering harmonious social interactions. Integrating these values into elementary and secondary school curricula requires a comprehensive approach that combines formal instruction, extracurricular activities, and real-life applications. Project-based learning, community service, and classroom discussions provide opportunities for students to practice ethical decision-making, cooperation, and empathy in meaningful contexts.Equally important is the role of educators as role models. Teachers and school staff must consistently demonstrate the values they aim to instill, as students often emulate the behaviors they observe in adults. Family involvement also significantly supports character formation, as parental guidance and consistent modeling of moral behavior reinforce the lessons learned at school.Despite its importance, implementing character education faces challenges, including curriculum constraints, insufficient teacher training, and cultural or environmental factors that may conflict with school initiatives. Addressing these challenges requires collaborative efforts among educators, parents, and policymakers to create supportive environments that nurture moral and social development. By instilling positive values early, students can grow into individuals who are academically competent, morally responsible, and socially aware, prepared to face future challenges with integrity and resilience